IMPLEMENTASI METODE MIND MAPPING MENGGUNAKAN ALAT FLASHCARD DITAMBAH LKPD WORD SQUARE TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS VIII DI SMP NEGERI SATAP WALATUNGGA - Yowa, Yohana Tangu; Ina, Anita Tamu; Makatita, Audrey Louse (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: This research is based on the researcher's findings on the application of learning methods or approaches at SMP Negeri Satap Walatungga which are ineffective so that students are less active and the level of student involvement in the learning process is low. This study aims to improve student learning outcomes through the application of the mind mapping method assisted by flashcard media equipped with LKPD word square Methods: This research is a Classroom Action Research (CAR) using a descriptive quantitative approach, conducted in three stages: pre-cycle, cycle I, and cycle II, involving 31 students. Data collection techniques include multiple-choice tests (posttest), observation, and documentation. Results: The cognitive learning outcomes in the pre-cycle showed an average score of 62.26, with 29% of students meeting the minimum mastery criteria (KKM), while 71% did not. The affective learning outcomes had an average score of 60.93, with 32% mastering the material and 68% not mastering it. In Cycle I, the cognitive average increased to 70.65, with 68% of students meeting the KKM and 32% not. The affective learning average rose to 68.10, with 65% mastering the material and 35% not, though the improvement was not yet optimal. In Cycle II, the cognitive average reached 80.32, with 84% meeting the KKM and 16% not. The affective learning average was 77.42, with 84% mastering the material and 16% not, showing significant improvement in both aspects. Conclusion: The application of the Mind Mapping method supported by Flashcard media and supplemented with LKPD Word Square can improve the learning outcomes of eighth-grade students at SMP Negeri Satap Walatungga.